PENINGKATAN KUALITAS MANAJEMEN SUMBER DAYA MANUSIA DI PUSKESMAS KUTA UTARA MELALUI PELATIHAN APLIKASI SOFTWARE WORKLOAD INDICATOR OF STAFFING NEED - Wardani, Silvia Intan (STIKES Advaita Medika Tabanan, 2025)
Puskesmas as the vanguard of health services in Indonesia face complex human resource (HR) challenges, including quantity, quality, and distribution. Suboptimal human resource planning is one of the factors that cause the inadequacy of health human resources. Training and development of employees at the Puskesmas is crucial to increase the competence and potential of individuals as valuable assets of the organization. This community service activity aims to improve the quality of human resource management at the Puskesmas Kuta Utara, involving 25 participants. The methods used include pre-test, providing material on workload calculation and HR management, simulating the use of WSN software, training sessions with case studies from participating health centers, and interactive discussions. The evaluation was carried out through a post-test with the same questions as the pre-test to measure the improvement of participants' understanding. The results of the activity are expected to make a positive contribution to improving the quality of human resource management and the effectiveness of health services at the Puskesmas Kuta Utara.